The effect of nitrogen fertilization and bacterial inoculum on some phenological and qualitative characteristics of Lupinus albus under conditions of Lattakia governorate - ديوب, علي; ياسر علي حماد,; حلا علي محمد , (Latakia University Journal -Biological Sciences Series, 2023)
The research was carried out in Snobar Jableh, 15 km from Lattakia city, in the two growing seasons 2018-2019 and 2019-2020 to demonstrate the effect of several levels of nitrogen fertilization (0-20 40-60-80 kg/ha) and bacterial inoculation with (Rh. Lupinii - Nitropin (Rh.Lupinii + Nitropin) and some phenological and specific characteristics of the white lupine plant. The study showed the following: Significant increase in the number of days from sowing until entering flowering and maturity and the percentage of protein in the seeds with an increase in the level of nitrogen fertilization from 0 to 80 kg / h and a decrease in the weight of the biological crop by increasing the level of nitrogen fertilization from 60 - 80 kg / h. e. The cause of bacterial inoculation using (Rh.Lupinii + Nitropin) for a significant increase in all studied traits. The reason for the joint interaction between the level of nitrogen fertilization 80 kg/ha and the bacterial inoculation (Rh.Lupinii + Nitropin) for a significant increase in the number of days from sowing to flowering and maturity and the percentage of protein in the seeds, and the interaction between the level of nitrogen fertilization 60 kg/ha led And bacterial inoculation (Rh.Lupinii + Nitropin) for asignificant increas in biological yield.